Chromosomal-level genome assembly of solitary bee pollinator Osmia excavata Alfken (Hymenoptera: Megachilidae) - Ruijuan Wang; Xiaoyan Dai; Shan Zhao; Zhenjuan Yin; Long Su; Chengxing Wang; Hao Chen; Li Zheng; Yan Liu; Yifan Zhai (Scientific Data)
Abstract Osmia spp. is a genus of solitary bees that serves as excellent pollinators for various fruit trees and has the potential to enhance pollination services in both agricultural and natural ecosystems. However, the absence of high-quality genomic resources limits our insights into evolutionary biology and ecological adaptations of Osmia. Here, we present a chromosome-level genome of Osmia excavata, using PacBio, Illumina, and Hi-C data. The genome has a total size of 164.35 Mb, with a scaffold N50 of 9.81 Mb, and the majority of contigs (98.50%, 161.88 Mb) are organized into sixteen chromosomes. BUSCO analysis reveals a completeness score of 99.7% (n = 1,367), with 99.6% identified as single-copy BUSCOs and 0.1% as duplicated BUSCOs. The genome contains 13.46% (22.11 Mb) repetitive elements and encodes 11,452 predicted protein-coding genes. This study provides a crucial genomic resource for our understanding of solitary bees’ evolution and ecological roles.